Evolution and Distribution of the ospC Gene, a Transferable Serotype Determinant of Borrelia burgdorferi - Alan G. Barbour (American Society for Microbiology, 2010)
ABSTRACT Borrelia burgdorferi, an emerging bacterial pathogen, is maintained in nature by transmission from one vertebrate host to another by ticks. One of the few antigens against which mammals develop protective immunity is the highly polymorphic OspC protein, encoded by the ospC gene on the cp26 plasmid. Intragenic recombination among ospC genes is known, but the extent to which recombination extended beyond the ospC locus itself is undefined. We accessed and supplemented collections of DNA sequences of ospC and other loci from ticks in three U.S. regions (the Northeast, the Midwest, and northern California); a total of 839 ospC sequences were analyzed. Three overlapping but distinct populations of B. burgdorferi corresponded to the geographic regions. In addition, we sequenced 99 ospC flanking sequences from different lineages and compared the complete cp26 sequences of 11 strains as well as the cp26 bbb02 loci of 56 samples. Besides recombinations with traces limited to the ospC gene itself, there was evidence of lateral gene transfers that involved (i) part of the ospC gene and one of the two flanks or (ii) the entire ospC gene and different lengths of both flanks. Lateral gene transfers resulted in different linkages between the ospC gene and loci of the chromosome or other plasmids. By acquisition of the complete part or a large part of a novel ospC gene, an otherwise adapted strain would assume a new serotypic identity, thereby being comparatively fitter in an area with a high prevalence of immunity to existing OspC types. IMPORTANCE The tick-borne zoonosis Lyme borreliosis is increasing in incidence and spreading geospatially in North America. Further understanding of the evolution and genetics of its cause, Borrelia burgdorferi, in its environments fosters progress toward ecologically based control efforts. By means of DNA sequencing of a large sample collection of the pathogen from across the United States, we studied the gene for the bacterium's highly diverse OspC protein, protective immunity against which develops in animals. We found that the distributions and frequencies of types of OspC genes differed between populations of B. burgdorferi in the Northeast, the Midwest, and California. Over time, OspC genes were transferred between strains through recombinations involving the whole or parts of the gene and one or both flanks. Acquisitions of OspC genes that are novel for the region confer to recipients unique identities to host immune systems and, presumably, selective advantage when immunity to existing types is widespread among hosts.